If f(4) = 8, g(4) = 2, f(−4) = 1, g(−4) = 3, f '(4) = 10, g '(4) = 12, f '(−4) = 6, and g '(−4) = −2, find H '(4) where H(x) = g( f(x) − 3x ) .
Follow Math Help Forum on Facebook and Google+
Originally Posted by kwivo If f(4) = 8, g(4) = 2, f(−4) = 1, g(−4) = 3, f '(4) = 10, g '(4) = 12, f '(−4) = 6, and g '(−4) = −2, find H '(4) where H(x) = g( f(x) − 3x ) . By the Chain Rule: $\displaystyle H(x) = g(f(x) - 3x)$ $\displaystyle \Rightarrow H'(x) = g'(f(x) - 3x) \cdot (f'(x) - 3)$ now just plug in numbers, and you're done
View Tag Cloud